Self-Confidence and Self-Awareness and Interpersonal Communication and Career Development: Self-Confidence and Self-Awareness Toward Interpersonal Communication and Career Development - Yolanda, Wafa; Hadi, Inthomy; Permata, Ayu Novalia; Widyaningrum, Adelia Eka; Susilowati, Endah; Jabarudin, Ismail; Lusiana, Nova; Andyarini, Esti Novi (Journal of Research and Measurement in Psychology: JPPP, 2021)
For an individual, self-awareness’ functions is to control all emotions, so that they can be used in establishing social relationships with other people, as well as to control oneself in an effort to meet their daily needs, so that they can successfully solve the problems they have. This study aims to find the relationship between self-confidence and self-awareness on interpersonal communication and career development of students of the Faculty of Psychology and Health, UIN Sunan Ampel Surabaya. This study used descriptive quantitative approach with variables: self confidence, self awareness, effective communication, and career development. The sample used in this study were 183 respondents who were randomly selected using a questionnaire, to students of the psychology faculty at UIN Sunan Ampel Surabaya. The descriptive data in this research is interpreted and analysed by using a scale range. In descriptive quantitative research, data processing is carried out based on percentage analysis and trend analysis. The results showed that there is relation between self-confidence and self-awareness on interpersonal communication and career development, where the higher the self-confidence and self-awareness that students have, then the higher the interpersonal communication skills and career development.